Pengaruh Motivasi terhadap Kinerja Karyawan Dimediasi oleh Kepuasan Kerja di Hotel Pita Maha Ubud - I Wayan Gede Aditya Kusuma; I Gusti Ayu Dewi Adnyani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of job satisfaction in mediating the effect of motivation on employee performance at Pita Maha Ubud Hotel. This study is based on motivation theory as a conceptual foundation. The sampling method used is non-probability sampling with a purposive sampling approach, resulting in a total of 84 respondents. The analytical techniques employed include path analysis, classical assumption tests, Sobel test, and VAF test. The findings indicate that motivation has a positive and significant impact on employee performance at Pita Maha Ubud Hotel; motivation also positively and significantly affects job satisfaction at Pita Maha Ubud Hotel; job satisfaction positively and significantly influences employee performance at Pita Maha Ubud Hotel; and job satisfaction partially mediates the relationship between motivation and employee performance at Pita Maha Ubud Hotel.